2011
DOI: 10.1002/adma.201003734
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Printing of Electrically Small Antennas on Three‐Dimensional Surfaces

Abstract: Increasingly stringent design constraints imposed by compact wireless devices for telecommunications, defense, and aerospace systems require the miniaturization of antennas. Unlike most electronic components, which benefi t from decreased size, antennas suffer limitations in gain, effi ciency, system range, and bandwidth when their size is reduced below a quarter-wavelength. The electrical size of the antenna is measured by its ka value, where k is the wavenumber ( k = 2 π / λ , λ = wavelength at the operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
388
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 546 publications
(396 citation statements)
references
References 24 publications
6
388
0
2
Order By: Relevance
“…The quality factor Q of the designed antenna is 26.03, approaching the lower physical bound of electrically small electric antennas at a given electrical size [14]. It is found that the radiation efficiency is improved when compared with the antenna in [12], which is built by printing silver nanoparticle ink on a hemispherical dielectric surface. It shows 71% radiation efficiency at ka of 0.46.…”
Section: Antenna Designmentioning
confidence: 77%
See 2 more Smart Citations
“…The quality factor Q of the designed antenna is 26.03, approaching the lower physical bound of electrically small electric antennas at a given electrical size [14]. It is found that the radiation efficiency is improved when compared with the antenna in [12], which is built by printing silver nanoparticle ink on a hemispherical dielectric surface. It shows 71% radiation efficiency at ka of 0.46.…”
Section: Antenna Designmentioning
confidence: 77%
“…The meander design is prevalent due to its intuitiveness in achieving a small form factor. It has been found that the 3D printed FSM antenna shows superior radiation efficiency when compared with the antenna in [12] due to the advantageous 3DP manufacturing technology. Some preliminary simulation results are shown in [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 However, keeping in mind the commercialization of the technology, manual fabrication of small-sized helixes is economically questionable. Therefore, advanced fabrication technologies, for example, conformal printing, 21 microcontact printing 22,23 and rolled-up strain engineering, [24][25][26][27][28] were suggested and applied to realize metallic and semiconducting helixes with linear dimensions in the tens of micrometer range. However, simple, precise, large-scale and high-yield fabrication of highperformance helical antennas that are compact but remain impedance matched to standard 50 Ω electronics is challenging and has not yet been achieved, thus preventing the commercial realization of smart implants.…”
Section: Introductionmentioning
confidence: 99%
“…For complicated antenna geometries such as conformal arrays full wave analysis and rigorous electromagnetic analysis is indispensable [12]. Conformal antenna arrays are utilized in airborne and space vehicles and also find applications in situations where surface adaptation is required (e.g., environmentally friendly cellular base stations) or flexible substrates [13][14][15]. Several conformal antennas have been suggested for MIMO use focusing only on mutual coupling but without any capacity calculations [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%